The impact of attitude toward watershed management operation on level of people participation - Golrang, Bahram Mohammadi; Lai, Food See; Rostami, Mohammad; Mohd Noor, Khamurudin; Abd. Kudus, Kamziah; Mashayekhi, Mojgan; Bagherian, Reza (Science Publications, 2012)
Recent studies in many countries had display the influence of many factors including: Satisfaction, Knowledge, Demographic and Attitudinal variables in level of people participation. The main question here is, whether these factors would also be effective on people participation in Iran? The purpose of this research was to investigate communication factors influencing attitudes of farmers’ application of Watershed Management Operations (WMO) in the Kushk-Abad watershed in Khorassan Razavi Province of Iran (85 km2). The general objective of this study is to assess factors that influence people’s participation in Iran. The study consist of all farmers in watershed study (N = 1500), of which 200 is selected through proportionate stratified random sampling technique (n = 200). The study was a descriptive-co relational, survey research. In fact, this research was designed to assess relationship between attitude toward Watershed Management Operations (WMO) and the level of participation in WMO in Iran. In order to obtain this aim, a cross sectional survey was applied. Data for this research collected through personal interviews from three villages in Kushk-Abad sub basin in Iran. The scale of attitude toward WMO and Participation in WMO were in order 0.71 and 0.92. Findings in the study indicated that a majority of the farmers have positive attitude toward adaption of WMO. The results revealed that the level of the participation of WMO is moderate and there is a significant and positive correlation between farmers’ attitudes towards application of watershed management operations. However based on the findings, the level of economical participation of people are the more than social and environmental participation. Moreover, the results indicated that the level of the respondents’ attitude towards WMO is moderate to low. This study also proved that participation in WMO is positively and significantly correlated with attitude toward WMO (r = 0.534, p = 0.000).